Social Entrepreneurship and Its Role on Building Societal Values in Malaysia - Mhd. Sarif, Suhaimi; Sarwar, Abdullah Al-Mamun; Azam, S. M. Ferdous (Kulliyyah of Economics and Management Sciences, IIUM, 2021)
This chapter postulates that social entrepreneurship has a role in building societal values. The subject social entrepreneur and social entrepreneurship are increasingly important. The economic functional analysis of entrepreneurship focuses upon the economic role for social entrepreneurship to drive social-based economic development. More recently, observers of the phenomenon of social entrepreneurship have suggested that social entrepreneurship involves creation of wealth through building new enterprises and that the social entrepreneur is the founder. The motivation behind wealth creation includes personal desire, self-motivation to engage in social work, and entrepreneurial spirits.